PERAN PSYCHOLOGICAL WELL-BEING AND PSYCHOLOGICAL RESILIENSI DALAM MEMPREDIKSI TINGKAT JUVENILE DELINQUENT REMAJA - Nur Fitriyani Hardi; Citra Widyastuti (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2026)
Adolescents are not a source of problems but an asset that needs to be developed. They need positive psychological conditions in an effort to strengthen their identity and self-development. Psychological well-being is the basis for completing developmental tasks in order to bring out the positive potentials of adolescents. Psychological well-being has a positive relationship with psychological resilience. A person is said to have psychological resilience if they can face difficulties, have psychological well-being, and life satisfaction.  Both are the basis for adolescents in facing internal (self) and external (external environment) challenges. This will enable them to resist negative external influences such as juvenile delinquents. The purpose of this study was to determine the effect of psychological well-being and psychological resilience on potential juvenile delinquent behavior. This study uses a quantitative approach with data collection using the psychological well-being scale, psychological resilience scale, and juvenile delinquent scale. The subjects in this study were adolescents at the junior high school level totaling 569 students at SMPN 6 Pontianak. Data analysis techniques used simple regression analysis and ANOVA on SPSS 22.0 for window. The results showed that separately there is a significant influence between psychological well-being on juvenile delinquent, and there is also a significant influence between psychological resilience on juvenile delinquent. So that simultaneously there is an influence of psychological well-being and psychological resilience on the potential for juvenile delinquent in adolescents in Kubu Raya Regency, West Kalimantan. That is, the higher the psychological well-being and psychological resilience, the lower the potential for juvenile delinquent in adolescents. Vice versa, the lower the psychological well-being and psychological resilience, the higher the potential for juvenile delinquent in adolescents.